Mosquito-repellent cream

By using cream base and DEET nanoparticles wrapped in carboxymethyl chitosan derivatives in DEET cream, the problems of unstable sustained release effect and poor skin feeling in existing DEET cream products are solved, and a longer-lasting and stable mosquito repellent effect is achieved.

CN119548423APending Publication Date: 2025-03-04GUANGZHOU CHIYANG SCENT TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411859289.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

When used outdoors, the sustained release effect of existing mosquito evaporation cream products is unstable, the skin feels poor, and the particle size of the mosquito repellent is difficult to control, resulting in poor mosquito repellent effect.

Method used

Deletes with cream-based base contain DEET and DEET nanoparticle suspensions. The average particle size of the nanoparticles is between 100 nm and 300 nm. Deletes are encapsulated by a complex of carboxymethyl chitosan derivatives and calcium ions, and photoresponsive groups are introduced to control the release rate of nanoparticles.

Benefits of technology

The uniform dispersion and stable release of DEET is achieved, which extends the mosquito repellent time, improves the user experience, and shows a more stable sustained release effect in outdoor environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119548423A_ABST
    Figure CN119548423A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of mosquito repellent products, and particularly provides mosquito repellent cream. Comprising 15 to 25 parts of stearic acid, 10 to 25 parts of paraffin, 2 to 6 parts of cetyl stearic acid, 2 to 6 parts of hexadecanol, 1 to 5 parts of glycerin monostearate, 5 to 15 parts of polyethylene glycol monostearate, 1 to 10 parts of glycerin, 40 to 80 parts of water, 5 to 15 parts of cross-linked polyvinylpyrrolidone, 20 to 40 parts of deet and 20 to 40 parts of a deet nanoparticle suspension. According to the mosquito-repellent cream disclosed by the invention, the deet and the deet nanoparticles can be uniformly and stably dispersed in the cream body, so that the effective mosquito-repellent time of the mosquito-repellent cream is long, and the use experience is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of mosquito repellent products, and particularly relates to a mosquito repellent cream. Background Art

[0002] DEET is a widely used mosquito repellent. Products with DEET as the main mosquito repellent ingredient rely on the emission of DEET to be effective, but DEET is emitted quickly and has a short shelf life after one application. In order to prolong the mosquito repellent effect of mosquito repellent products, long-lasting mosquito repellent products in the prior art are mostly cream-like in texture with strong adhesion. Furthermore, there is also a practice of using a carrier to encapsulate DEET to delay its release. For example, the American Sawyer mosquito repellent cream uses submicron encapsulation technology to encapsulate DEET in a protein, and gradually releases DEET as the protein dissolves, thereby prolonging the effective mosquito repellent time after the product is applied. However, the dissolution rate of this protein carrier is difficult to control, especially in outdoor performance, and the sustained release effect is unstable.

[0003] In order to enhance outdoor performance, the existing mosquito repellent cream products usually adopt a formula with strong water resistance, which generally has the problem of poor skin feel. In addition, the particle size of the DEET encapsulated by the carrier is difficult to control and it is not easy to disperse it uniformly and stably in the cream product, which further leads to a decrease in the use feel of the mosquito repellent cream. A long-lasting mosquito repellent cream with improved use feel is needed. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a long-lasting mosquito repellent cream with improved use feeling.

[0005] The invention provides a mosquito repellent cream, which comprises, by weight, 15-25 parts of stearic acid, 10-25 parts of paraffin, 2-6 parts of spermaceti, 2-6 parts of hexadecanol, 1-5 parts of glyceryl monostearate, 5-15 parts of polyethylene glycol monostearate, 1-10 parts of glycerol, 40-80 parts of water, 5-15 parts of cross-linked polyvinyl pyrrolidone, 20-40 parts of DEET, and 20-40 parts of DEET nanoparticle suspension.

[0006] Preferably, the composition comprises, by weight, 17-23 parts of stearic acid, 17-23 parts of paraffin, 3-5 parts of cetyl stearic acid, 3-5 parts of hexadecanol, 2-4 parts of glyceryl monostearate, 7-13 parts of polyethylene glycol monostearate, 4-8 parts of glycerol, 50-70 parts of water, 7-13 parts of cross-linked polyvinyl pyrrolidone, 25-35 parts of DEET, and 25-35 parts of DEET nanoparticle suspension.

[0007] Preferably, the composition comprises, by weight, 19-21 parts of stearic acid, 19-21 parts of paraffin, 3.5-4.5 parts of cetearyl stearic acid, 3.5-4.5 parts of hexadecanol, 2.5-3.5 parts of glyceryl monostearate, 9-11 parts of polyethylene glycol monostearate, 5-7 parts of glycerol, 58-68 parts of water, 9-11 parts of cross-linked polyvinyl pyrrolidone, 28-32 parts of DEET, and 28-32 parts of DEET nanoparticle suspension.

[0008] Preferably, the DEET nanoparticle suspension contains nanoparticles, and an average particle size x of the nanoparticles satisfies 100 nm≤x≤300 nm.

[0009] Preferably, the DEET nanoparticle suspension comprises nanoparticles, wherein the nanoparticles are formed by encapsulating DEET with a complex of a carboxymethyl chitosan derivative and calcium ions; the carboxymethyl chitosan derivative is prepared by modifying carboxymethyl chitosan with a compound having a photoresponsive group, wherein the photoresponsive group is a cinnamic acid group, a coumarin group or an azobenzene group. Carboxymethyl chitosan has hydrophilicity and good biocompatibility, is easy to prepare nanoparticles, and can provide a good skin feel when added to daily chemical products. After the photoresponsive group is introduced into carboxymethyl chitosan, it has photosensitivity.

[0010] Preferably, the carboxymethyl chitosan derivatives include compounds O-CMC-CA, O-CMC-CM and O-CMC-CZ, and the structural formula of O-CMC-CA is as follows:

[0011]

[0012] More preferably, a=50, b=50

[0013] The structural formula of the O-CMC-CM is as follows:

[0014]

[0015] More preferably, a=50, b=50

[0016] The structural formula of the O-CMC-CZ is as follows:

[0017]

[0018] More preferably, a=50, b=50

[0019] Preferably, the DEET nanoparticle suspension is prepared by the following steps:

[0020] (1) Preparation of nano packaging materials:

[0021] S11: dissolving a monomer having a photoresponsive group in dimethyl sulfoxide, adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide, and stirring to activate the monomer in a light-proof condition;

[0022] S12: dissolving carboxymethyl chitosan in deionized water to prepare an aqueous solution;

[0023] S13: The solution obtained in S11 and the solution obtained in S12 are mixed, tetramethylethylenediamine is added, and the mixture is stirred and reacted at room temperature in the dark to obtain a light yellow transparent solution;

[0024] S14: dialyzing the solution obtained in S3 with deionized water;

[0025] S15: freeze-drying the product obtained in S14 to obtain the nano packaging material;

[0026] (3) Preparation of nanoparticle suspension:

[0027] S21: preparing the nano-package obtained in S15 into an aqueous solution to remove insoluble impurities;

[0028] S22: adjusting the pH of the solution obtained in S21 to 6.5-8;

[0029] S23: preparing a DEET ethanol solution, and adding the DEET ethanol solution dropwise into the solution obtained in S22;

[0030] S24: adding the calcium chloride solution dropwise to the solution obtained in S23, and continuing stirring until the reaction is complete;

[0031] S25: sedimentation under an inert atmosphere to obtain the DEET nanoparticle suspension.

[0032] Preferably, the monomer having a photoresponsive group is one or more of cinnamic acid, coumarin derivatives and azobenzene derivatives.

[0033] Preferably, the structural formula of the coumarin derivative is:

[0034]

[0035] Preferably, the structural formula of the azobenzene derivative is:

[0036]

[0037] Preferably, the mosquito repellent cream consists of 19-21 parts of stearic acid, 19-21 parts of paraffin, 3.5-4.5 parts of cetyl stearic acid, 3.5-4.5 parts of hexadecanol, 2.5-3.5 parts of glyceryl monostearate, 9-11 parts of polyethylene glycol monostearate, 5-7 parts of glycerol, 58-68 parts of water, 0.1-0.3 parts of Kaisong CG, 9-11 parts of cross-linked polyvinyl pyrrolidone, 28-32 parts of DEET, and 28-32 parts of DEET nanoparticle suspension.

[0038] Preferably, the preparation method of the mosquito repellent cream comprises the following steps:

[0039] S31: heating and mixing the stearic acid, paraffin, cetyl stearic acid, hexadecanol, glyceryl monostearate, and polyethylene glycol monostearate to obtain phase A; heating and mixing the glycerin and water to obtain phase B; mixing the cross-linked polyvinyl pyrrolidone and DEET to obtain phase C;

[0040] S32: mixing the phase A and the phase B in a homogenizer to obtain an emulsion;

[0041] S33: adding phase C into the homogenizer and mixing;

[0042] S34: putting the DEET nanoparticle suspension into the homogenizer for mixing.

[0043] The mosquito repellent cream described in the present application adopts a cream base, has good skin affinity, adhesion, stability and moisturizing effect, uses DEET as a mosquito repellent ingredient, and contains DEET and DEET nanoparticles. The DEET nanoparticles are added to the cream base in the form of a suspension. When used, DEET evaporates to achieve a mosquito repellent effect, and the nanoparticles gradually release the DEET wrapped therein, extending the effective mosquito repellent time of the DEET. In the mosquito repellent cream described in the present application, DEET and DEET nanoparticles can be evenly and stably dispersed in the cream body, and the mosquito repellent cream has a long effective mosquito repellent time and a good user experience. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] The above and other purposes, features and advantages of the present invention will become more clear by more specific description of the preferred embodiments of the present invention shown in the accompanying drawings. The same reference numerals indicate the same parts in all the accompanying drawings, and the accompanying drawings are not deliberately scaled to the actual size, and the focus is on illustrating the main purpose of the present invention.

[0045] Figure 1 is the HNMR spectrum of compound O-CMC-CA;

[0046] Figure 2 is the HNMR spectrum of compound CM;

[0047] Figure 3is the HNMR spectrum of compound O-CMC-CM;

[0048] Figure 4 is the HNMR spectrum of compound CZ;

[0049] Figure 5 is the HNMR spectrum of compound O-CMC-CZ;

[0050] Figure 6 (a) is the UV-visible spectra of O-CMC and O-CMC-CA, (b) is the UV-visible spectra of O-CMC and O-CMC-CM;

[0051] Figure 7 (a) is the UV-visible spectrum of O-CMC-CA, (b) is the fluorescence spectrum of O-CMC-CA;

[0052] Figure 8 (a) is the UV-visible spectrum of O-CMC-CM, (b) is the fluorescence spectrum of O-CMC-CM;

[0053] Fig. 9 It is the UV-visible spectrum of O-CMC-CZ;

[0054] Fig.10 (a) is the TGA curve of O-CMC and O-CMC-CA, (b) is the DTG curve of O-CMC and O-CMC-CA);

[0055] Fig.11 (a) is the TGA curve of O-CMC and O-CMC-CM, (b) is the DTG curve of O-CMC and O-CMC-CM;

[0056] Fig.12 (a) is the TGA curve of O-CMC and O-CMC-CZ, (b) is the DTG curve of O-CMC and O-CMC-CZ;

[0057] Fig.13 (a) is the XRD pattern of CA, O-CMC, O-CMC-CA, CMC-CA-Ca blank nanoparticles, and DEET / CMC-CA-Ca drug-loaded nanoparticles; (b) is the XRD pattern of CM, O-CMC, O-CMC-CM, CMC-CM-Ca blank nanoparticles, and DEET / CMC-CM-Ca drug-loaded nanoparticles; (c) is the XRD pattern of CZ, O-CMC, O-CMC-CZ, CMC-CZ-Ca blank nanoparticles, and DEET / CMC-CZ-Ca drug-loaded nanoparticles;

[0058] Fig.14(a) is the size distribution diagram of DEET / CMC-CA-Ca, (b) is the size distribution diagram of DEET / CMC-CM-Ca, and (c) is the size distribution diagram of DEET / CMC-CZ-Ca;

[0059] Fig.15 is a scanning electron microscope image of DEET / CMC-CA-Ca;

[0060] Fig.16 is a scanning electron microscope image of DEET / CMC-CM-Ca;

[0061] Fig.17 is a scanning electron microscope image of DEET / CMC-CZ-Ca;

[0062] Fig.18 (a) is the average particle size of nanoparticles (after illumination) prepared with different mass ratios of CaCl2 and O-CMC-CA, (b) is the average particle size of nanoparticles (after illumination) prepared with different mass ratios of CaCl2 and O-CMC-CM, (c) is the average particle size of nanoparticles prepared with different mass ratios of CaCl2 and O-CMC-CZ; (d) is the average particle size of nanoparticles prepared with different mass ratios of CaCl2 and O-CMC-CZ after ultraviolet light irradiation;

[0063] Fig.19 (a) is the retention curve of DEET / CMC-CA-Ca in PBS buffer, (b) is the cumulative release curve of DEET / CMC-CA-Ca in PBS buffer;

[0064] Fig. 20 (a) is the retention curve of DEET / CMC-CM-Ca in PBS buffer, (b) is the cumulative release curve of DEET / CMC-CM-Ca in PBS buffer;

[0065] Fig.21 (a) is the retention curve of DEET / CMC-CZ-Ca in PBS buffer, (b) is the cumulative release curve of DEET / CMC-CZ-Ca in PBS buffer;

[0066] Fig. 22 is the standard curve of DEET concentration and peak area;

[0067] Fig.23 (a) is the corresponding relationship curve between OCA indoor release time and peak area and release time and residual amount, (b) is the time-concentration comparison diagram of OCA and control group;

[0068] Fig.24(a) is the corresponding relationship curve between OCM indoor release time and peak area and release time and residual amount, (b) is the time-concentration comparison diagram of OCM and control group;

[0069] Fig.25 (a) is the corresponding relationship curve between the indoor release time and peak area of ​​OCZ and the release time and residual amount, (b) is the time-concentration comparison diagram of OCZ and control group;

[0070] Fig.26 (a) is the corresponding relationship curve between the outdoor release time and peak area of ​​OCA and the release time and the residual amount, (b) is the corresponding relationship curve between the outdoor release time and peak area of ​​OCM and the release time and the residual amount, (c) is the corresponding relationship curve between the outdoor release time and peak area of ​​OCZ and the release time and the residual amount;

[0071] Fig. 27 The mosquito repellent time concentration prediction graph for OCA and control groups;

[0072] Fig.28 This is the mosquito repellent time concentration prediction graph for OCM and control group;

[0073] Fig.29 This is the mosquito repellent time concentration prediction diagram for OCZ and control group. DETAILED DESCRIPTION

[0074] To facilitate understanding of the present invention, a more comprehensive description of the present invention will be given below with reference to the relevant drawings.

[0075] It should be noted that when an element is considered to be "connected" to another element, it may be directly connected to another element and integrated therewith, or there may be an intermediate element at the same time. The terms "installed", "one end", "the other end" and similar expressions used herein are for illustrative purposes only.

[0076] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art. The terms used in the specification herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0077] The invention provides a mosquito repellent cream, which comprises, by weight, 15-25 parts of stearic acid, 10-25 parts of paraffin, 2-6 parts of spermaceti, 2-6 parts of hexadecanol, 1-5 parts of glyceryl monostearate, 5-15 parts of polyethylene glycol monostearate, 1-10 parts of glycerol, 40-80 parts of water, 5-15 parts of cross-linked polyvinyl pyrrolidone, 20-40 parts of DEET, and 20-40 parts of DEET nanoparticle suspension.

[0078] The mosquito repellent cream described in the present application adopts a cream base, has good skin affinity, adhesion, stability and moisturizing effect, uses DEET as a mosquito repellent ingredient, and contains DEET and DEET nanoparticles. The DEET nanoparticles are added to the cream base in the form of a suspension, and after application, the nanoparticles are affected by temperature and gradually release the DEET wrapped therein, playing a slow-release effect. DEET and DEET nanoparticles can be evenly and stably dispersed in the cream body, and the mosquito repellent cream has a long effective mosquito repelling time and a good user experience.

[0079] In a preferred embodiment, the composition comprises, by weight, 17-23 parts of stearic acid, 17-23 parts of paraffin, 3-5 parts of cetyl stearic acid, 3-5 parts of hexadecanol, 2-4 parts of glyceryl monostearate, 7-13 parts of polyethylene glycol monostearate, 4-8 parts of glycerol, 50-70 parts of water, 7-13 parts of cross-linked polyvinyl pyrrolidone, 25-35 parts of DEET, and 25-35 parts of DEET nanoparticle suspension.

[0080] In a preferred embodiment, the composition comprises, by weight, 19-21 parts of stearic acid, 19-21 parts of paraffin, 3.5-4.5 parts of cetearyl stearic acid, 3.5-4.5 parts of hexadecanol, 2.5-3.5 parts of glyceryl monostearate, 9-11 parts of polyethylene glycol monostearate, 5-7 parts of glycerol, 58-68 parts of water, 9-11 parts of cross-linked polyvinyl pyrrolidone, 28-32 parts of DEET, and 28-32 parts of DEET nanoparticle suspension.

[0081] In a preferred embodiment, the DEET nanoparticle suspension contains nanoparticles, and the average particle size x of the nanoparticles satisfies 100 nm≤x≤300 nm.

[0082] In a preferred embodiment, the DEET nanoparticle suspension includes nanoparticles, wherein the nanoparticles are formed by encapsulating DEET with a complex of a carboxymethyl chitosan derivative and calcium ions; the carboxymethyl chitosan derivative is prepared by modifying carboxymethyl chitosan with a compound having a photoresponsive group, wherein the photoresponsive group is a cinnamic acid group, a coumarin group, or an azobenzene group. Carboxymethyl chitosan has hydrophilicity and good biocompatibility, is easy to prepare nanoparticles, and can provide a good skin feel when added to daily chemical products. After the photoresponsive group is introduced into carboxymethyl chitosan, it has photosensitivity.

[0083] In a preferred embodiment, the carboxymethyl chitosan derivatives include compounds O-CMC-CA, O-CMC-CM and O-CMC-CZ, and the structural formula of O-CMC-CA is as follows:

[0084]

[0085] In the preferred embodiment, a=50, b=50;

[0086] The structural formula of the O-CMC-CM is as follows:

[0087]

[0088] In the preferred embodiment, a=50, b=50;

[0089] The structural formula of the O-CMC-CZ is as follows:

[0090]

[0091] In the preferred embodiment, a=50, b=50;

[0092] In a preferred embodiment, the DEET nanoparticle suspension is prepared by the following steps:

[0093] (1) Preparation of nano packaging materials:

[0094] S11: dissolving the monomer having a photoresponsive group in dimethyl sulfoxide (DSMO), adding 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC·HCl) and N-hydroxysuccinimide (NHS), and stirring to activate in a dark environment;

[0095] S12: dissolving carboxymethyl chitosan (O-CMC) in deionized water to prepare an aqueous solution;

[0096] S13: The solution obtained in S11 and the solution obtained in S12 are mixed, tetramethylethylenediamine (TMEDA) is added, and the mixture is stirred and reacted at room temperature in the dark to obtain a light yellow transparent solution;

[0097] S14: dialyzing the solution obtained in S3 with deionized water;

[0098] S15: freeze-drying the product obtained in S14 to obtain the nano packaging material;

[0099] (2) Preparation of nanoparticle suspension:

[0100] S21: preparing the nano-package obtained in S15 into an aqueous solution to remove insoluble impurities;

[0101] S22: adjusting the pH of the solution obtained in S21 to 6.5-8;

[0102] S23: preparing a DEET ethanol solution, and adding the DEET ethanol solution dropwise into the solution obtained in S22;

[0103] S24: adding the calcium chloride solution dropwise to the solution obtained in S23, and continuing stirring until the reaction is complete;

[0104] S25: sedimentation under an inert atmosphere to obtain the DEET nanoparticle suspension.

[0105] In a preferred embodiment, a photosensitive group is implanted into carboxymethyl chitosan (O-CMC), so that the nano-packaging material portion of the DEET nanoparticles has a photosensitive property, and the speed of releasing DEET is affected by light.

[0106] In a preferred embodiment, the monomer having a photoresponsive group is one or more of cinnamic acid, coumarin derivatives and azobenzene derivatives.

[0107] When cinnamic acid (CA) is used as a monomer having a photoresponsive group, the nano packaging material is prepared by the following method:

[0108] S11: Weigh 4-5 parts of cinnamic acid (CA) by weight and dissolve it in dimethyl sulfoxide (DMSO), add 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC·HCl) and N-hydroxysuccinimide (NHS), and stir to activate under light-proof conditions;

[0109] S12: weigh 5-6 parts by weight of carboxymethyl chitosan (O-CMC) and dissolve them in deionized water to prepare an aqueous solution;

[0110] S13: The solution obtained in S11 and the solution obtained in S12 are mixed, tetramethylethylenediamine (TMEDA) is added, and the mixture is stirred and reacted at room temperature in the dark to obtain a light yellow transparent solution;

[0111] S14: dialyzing the solution obtained in S3 with deionized water;

[0112] S15: freeze-drying the product obtained in S14 to obtain the nano packaging material (O-CMC-CA).

[0113] In a preferred embodiment, the structural formula of the coumarin derivative is:

[0114]

[0115] The preparation method of the coumarin derivative is as follows:

[0116] S01: Weigh 3-5 parts of 2-bromoacetic acid, 1 part of 7-hydroxy-4-methylcoumarin, and 5-8 parts of potassium carbonate by weight, add a trace amount of potassium iodide, dissolve in ethanol, and heat to react;

[0117] S02: Take the product obtained in S01 and add deionized water to dissolve it, adjust the pH to 3, and remove the excess ethanol by rotary evaporation to produce a white precipitate;

[0118] S03: The product obtained in S02 was washed three times with deionized water, then washed with a sodium bicarbonate aqueous solution, and filtered under reduced pressure to obtain a white coumarin derivative powder (CM).

[0119] When the coumarin derivative is used as a monomer having a photoresponsive group, the nano packaging material is prepared by the following method:

[0120] S11: Weigh 11-16 parts of coumarin derivative (CM) by weight and dissolve them in dimethyl sulfoxide (DMSO), add 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC·HCl) and N-hydroxysuccinimide (NHS), and stir to activate under light-proof conditions;

[0121] S12: weigh 10-12 parts by weight of carboxymethyl chitosan (O-CMC) and dissolve them in deionized water to prepare an aqueous solution;

[0122] S13: The solution obtained in S11 and the solution obtained in S12 are mixed, tetramethylethylenediamine (TMEDA) is added, and the mixture is stirred and reacted at room temperature in the dark to obtain a light yellow transparent solution;

[0123] S14: dialyzing the solution obtained in S3 with deionized water;

[0124] S15: freeze-drying the product obtained in S14 to obtain the nano packaging material (O-CMC-CM).

[0125] In a preferred embodiment, the structural formula of the azobenzene derivative is:

[0126]

[0127] The preparation method of the azobenzene derivative is as follows:

[0128] S01: Weigh 1 part of 4-phenylazophenol, 4-6 parts of 6-bromohexanoic acid, 5-9 parts of potassium carbonate and a trace amount of potassium iodide, add ethanol, and heat to react;

[0129] S02: Take the product obtained in S01 and add deionized water to dissolve it, adjust the pH to 3-4, and a yellow precipitate will appear;

[0130] S03: The product obtained in S02 was cooled at -20°C, filtered under reduced pressure, and washed four times with dichloromethane and petroleum ether;

[0131] S04: The product obtained in S03 is vacuum dried and then recrystallized using hot acetonitrile to obtain an azobenzene derivative (CZ).

[0132] When the azobenzene derivative is used as a monomer having a photoresponsive group, the nano packaging material is prepared by the following method:

[0133] S11: 17-23 parts of an azobenzene derivative (CZ) are weighed and dissolved in dimethyl sulfoxide (DMSO), 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC·HCl) and N-hydroxysuccinimide (NHS) are added, and the mixture is stirred and activated in a dark environment;

[0134] S12: weigh 10-14 parts by weight of carboxymethyl chitosan (O-CMC) and dissolve them in deionized water to prepare an aqueous solution;

[0135] S13: The solution obtained in S11 and the solution obtained in S12 are mixed, tetramethylethylenediamine (TMEDA) is added, and the mixture is stirred and reacted at room temperature in the dark to obtain a light yellow transparent solution;

[0136] S14: dialyzing the solution obtained in S3 with deionized water;

[0137] S15: freeze-drying the product obtained in S14 to obtain the nano packaging material (O-CMC-CZ).

[0138] In a preferred embodiment, the mosquito repellent cream consists of, by weight, 19-21 parts of stearic acid, 19-21 parts of paraffin, 3.5-4.5 parts of cetyl stearic acid, 3.5-4.5 parts of hexadecanol, 2.5-3.5 parts of glyceryl monostearate, 9-11 parts of polyethylene glycol monostearate, 5-7 parts of glycerol, 58-68 parts of water, 0.1-0.3 parts of Kaisong CG, 9-11 parts of cross-linked polyvinyl pyrrolidone, 28-32 parts of DEET, and 28-32 parts of DEET nanoparticle suspension.

[0139] In a preferred embodiment, the method for preparing the mosquito repellent cream comprises the following steps:

[0140] S31: heating and mixing the stearic acid, paraffin, cetyl stearic acid, hexadecanol, glyceryl monostearate, and polyethylene glycol monostearate to obtain phase A; heating and mixing the glycerin and water to obtain phase B; mixing the cross-linked polyvinyl pyrrolidone and DEET to obtain phase C;

[0141] S32: mixing the phase A and the phase B in a homogenizer to obtain an emulsion;

[0142] S33: adding phase C into the homogenizer and mixing;

[0143] S34: putting the DEET nanoparticle suspension into the homogenizer for mixing.

[0144] In order to have a further understanding and recognition of the technical solution of the present invention, several preferred embodiments are listed and described in further detail.

[0145] Example 1

[0146] Prepare a suspension of DEET nanoparticles as follows:

[0147] (1) Preparation of nano packaging materials:

[0148] S11: 0.148 g (1 mmol) of cinnamic acid (CA) was weighed and dissolved in 5 mL of dimethyl sulfoxide (DSMO), and 0.191 g (1 mmol) of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC·HCl) and 0.115 g (1 mmol) of N-hydroxysuccinimide (NHS) were added in sequence, and stirred for 4 hours in a dark environment;

[0149] S12: Weigh 0.181 g (0.333 mmol) of carboxymethyl chitosan (O-CMC) and stir thoroughly to dissolve it in 20 mL of deionized water;

[0150] S13: Add the solution obtained in S11 to the solution obtained in S12, and then add 1 mL of tetramethylethylenediamine (TMEDA), and stir at 25°C in the dark for 24 h to obtain a light yellow transparent solution;

[0151] S14: After the reaction, the product obtained in S13 was dialyzed extensively in deionized water for 48 h;

[0152] S15: freeze-drying the product obtained in S14 to obtain the nano packaging material O-CMC-CA.

[0153] The structural formula of cinnamic acid (CA) is as follows:

[0154]

[0155] The HNMR spectrum of O-CMC-CA is shown in Figure 1 As shown, its synthetic route is as follows:

[0156]

[0157] Where a=50, b=50, n=50;

[0158] (2) Preparation of nanoparticle suspension:

[0159] S21: The nano packaging material O-CMC-CA obtained in S15 is prepared into an aqueous solution, dissolved in water to prepare a 2 mg / mL solution, and then the solution is frozen at 0° C. for 30 minutes after removing insoluble impurities.

[0160] S22: The pH of the solution obtained in S21 was adjusted to 7.3 using 0.1 mol / L HCl solution;

[0161] S23: preparing a 25 mg / mL DEET ethanol solution and freeze-drying it, and adding the DEET ethanol solution dropwise to the solution obtained in S22;

[0162] S24: Prepare a calcium chloride solution with a concentration of 2 mg / mL, and use a 1 mL syringe to drop the calcium chloride solution into the solution obtained in S23 at a rate of one drop per two seconds, and continue stirring for 30 minutes. The mass ratio of calcium chloride to O-CMC-CA used is 1:4;

[0163] S25: Settling for one hour under an inert atmosphere to obtain a DEET nanoparticle suspension, wherein the DEET nanoparticles are DEET / CMC-CA-Ca.

[0164] Example 2

[0165] Prepare a suspension of DEET nanoparticles as follows:

[0166] First, prepare the coumarin derivative (CM):

[0167] S01: Weigh 1.58 g (11.37 mmol) of 2-bromoacetic acid, 0.4 g (2.2 mmol) of 7-hydroxy-4-methylcoumarin, 3.14 g (22 mmol) of potassium carbonate and a trace amount of potassium iodide, add 70 mL of ethanol and ultrasonically dissolve, and heat in an oil bath at 75°C for 24 h;

[0168] S02: Take the product obtained in S01 and add deionized water to dissolve it, adjust the pH to 3, and remove the excess ethanol by rotary evaporation to produce a white precipitate;

[0169] S03: The product obtained in S02 was washed three times with deionized water and once with a saturated sodium bicarbonate aqueous solution, and filtered under reduced pressure to obtain a white coumarin derivative powder.

[0170] In this example, 0.268 g of white coumarin derivative powder was obtained with a yield of 52%.

[0171] The structural formula of CM is as follows:

[0172] The HNMR spectrum of CM is shown in Figure 2 As shown, its synthetic route is as follows:

[0173]

[0174] Where a=50, b=50, n=50;

[0175] Then start preparing nanoparticles:

[0176] (1) Preparation of nano packaging materials:

[0177] S11: 0.234 g (1 mmol) of coumarin derivative (CM) was weighed and dissolved in 5 mL of dimethyl sulfoxide (DSMO), and 0.191 g (1 mmol) of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC·HCl) and 0.115 g (1 mmol) of N-hydroxysuccinimide (NHS) were added in sequence, and the mixture was stirred for 4 hours in a dark environment;

[0178] S12: Weigh 0.181 g (0.333 mmol) of carboxymethyl chitosan (O-CMC) and stir thoroughly to dissolve it in 20 mL of deionized water;

[0179] S13: Add the solution obtained in S11 to the solution obtained in S12, and then add 1 mL of tetramethylethylenediamine (TMEDA), and stir at 25°C in the dark for 24 h to obtain a light yellow transparent solution;

[0180] S14: After the reaction, the product obtained in S13 was dialyzed extensively in deionized water for 48 h;

[0181] S15: freeze-drying the product obtained in S14 to obtain the nano packaging material O-CMC-CM.

[0182] The HNMR spectrum of O-CMC-CM is shown in Figure 3 Shown, its synthetic route is as follows:

[0183]

[0184] Where a=50, b=50, n=50;

[0185] (2) Preparation of nanoparticle suspension:

[0186] S21: dissolving the nano-packaging material O-CMC-CM obtained in S15 in water to prepare a 2 mg / mL solution, removing insoluble impurities and freezing at 0°C for 30 minutes;

[0187] S22: The pH of the solution obtained in S21 was adjusted to 7.3 using 0.1 mol / L HCl solution;

[0188] S23: preparing a 25 mg / mL DEET ethanol solution and freeze-drying it, and adding the DEET ethanol solution dropwise to the solution obtained in S22;

[0189] S24: Prepare a calcium chloride solution with a concentration of 2 mg / mL, and use a 1 mL syringe to drop the calcium chloride solution into the solution obtained in S23 at a rate of one drop per two seconds, and continue stirring for 30 minutes. The mass ratio of calcium chloride to O-CMC-CM used is 1:4;

[0190] S25: Settling for one hour under an inert atmosphere to obtain a DEET nanoparticle suspension, wherein the DEET nanoparticles are DEET / CMC-CM-Ca.

[0191] Example 3

[0192] Prepare a suspension of DEET nanoparticles as follows:

[0193] First, prepare the azobenzene derivative (CZ):

[0194] S01: Weigh 0.198 g (1 mmol) of 4-phenylazophenol, 0.975 g (5 mmol) of 6-bromohexanoic acid, 1.382 g (10 mmol) of potassium carbonate and a trace amount of potassium iodide, add 20 mL of ethanol, and heat in an oil bath at 75°C for 24 h;

[0195] S02: Take the product obtained in S01 and add deionized water to dissolve it, adjust the pH to 3-4, and a yellow precipitate will appear;

[0196] S03: The product obtained in S02 was cooled at -20°C, filtered under reduced pressure, and washed four times with dichloromethane and petroleum ether;

[0197] S04: The product obtained in S03 is vacuum dried and then recrystallized using hot acetonitrile to obtain an azobenzene derivative CZ.

[0198] In this example, the yield of the azobenzene derivative is 45%.

[0199] The HNMR spectrum of CZ is shown in Figure 4 As shown, its synthetic route is as follows:

[0200]

[0201] Then start preparing nanoparticles:

[0202] (1) Preparation of nano packaging materials:

[0203] S11: 0.312 g (1 mmol) of an azobenzene derivative (CZ) was weighed and dissolved in 5 mL of dimethyl sulfoxide (DSMO), and 0.191 g (1 mmol) of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC·HCl) and 0.115 g (1 mmol) of N-hydroxysuccinimide (NHS) were added in sequence, and the mixture was stirred for 4 hours in a dark environment;

[0204] S12: Weigh 0.181 g (0.333 mmol) of carboxymethyl chitosan (O-CMC) and stir thoroughly to dissolve it in 20 mL of deionized water;

[0205] S13: Add the solution obtained in S11 to the solution obtained in S12, and then add 1 mL of tetramethylethylenediamine (TMEDA), and stir at 25°C in the dark for 24 h to obtain a light yellow transparent solution;

[0206] S14: After the reaction, the product obtained in S13 was dialyzed extensively in deionized water for 48 h;

[0207] S15: freeze-drying the product obtained in S14 to obtain the nano packaging material O-CMC-CZ.

[0208] The HNMR spectrum of 0-CMC-CZ is as follows Figure 5 As shown, its synthetic route is as follows:

[0209]

[0210] Where a=50, b=50, n=50;

[0211] (2) Preparation of nanoparticle suspension:

[0212] S21: The nano packaging material O-CMC-CZ obtained in S15 was dissolved in water to prepare a 2 mg / mL solution, and the solution was frozen at 0°C for 30 minutes after removing insoluble impurities.

[0213] S22: The pH of the solution obtained in S21 was adjusted to 7.3 using 0.1 mol / L HCl solution;

[0214] S23: preparing a 25 mg / mL DEET ethanol solution and freeze-drying it, and adding the DEET ethanol solution dropwise to the solution obtained in S22;

[0215] S24: Prepare a calcium chloride solution with a concentration of 2 mg / mL, use a 1 mL syringe to drop the calcium chloride solution into the solution obtained in S23 at a rate of one drop per two seconds, and continue stirring for 30 minutes. The mass ratio of calcium chloride to O-CMC-CZ used is 1:4;

[0216] S25: Settling for one hour under an inert atmosphere to obtain a DEET nanoparticle suspension, wherein the DEET nanoparticles are DEET / CMC-CZ-Ca.

[0217] Example 4

[0218] Preparation of mosquito repellent cream

[0219] The DEET nanoparticle suspension prepared in Example 1-3 was used to prepare mosquito repellent cream according to the following preparation method.

[0220] The preparation method is as follows:

[0221] S31: In parts by weight, 20 parts of stearic acid, 20 parts of liquid paraffin, 4 parts of cetearyl alcohol, 4 parts of hexadecanol, 3 parts of glyceryl monostearate, and 10 parts of polyethylene glycol monostearate are weighed in a first reaction container, heated to 85°C and mixed evenly to obtain phase A; 6 parts of glycerol, 63 parts of distilled water, and 0.2 parts of Kaisong CG are weighed in a second reaction container, heated to 90°C and mixed evenly to obtain phase B; 10 parts of polyvinyl pyrrolidone and 30 parts of DEET are weighed in a third reaction container and mixed evenly to obtain phase C;

[0222] S32: Pour phase B into phase A and homogenize using a high-speed homogenizer for 5 minutes to obtain an emulsion;

[0223] S33: After the emulsion obtained in S32 is cooled to 45° C., phase C is added to the high-speed homogenizer and stirred until uniform;

[0224] S34: Weigh 30 parts of DEET nanoparticle suspension, add it into the high-speed homogenizer and continue stirring until the mixture is uniform. After the mixture is cooled to 35° C., stop stirring and cool it to room temperature.

[0225] The mosquito repellent cream prepared by adding the DEET nanoparticle suspension obtained in Example 1 is OCA, the mosquito repellent cream prepared by adding the DEET nanoparticle suspension obtained in Example 2 is OCM, and the mosquito repellent cream prepared by adding the DEET nanoparticle suspension obtained in Example 3 is OCZ.

[0226] The following is an evaluation of each embodiment from different perspectives.

[0227] Test Item 1: UV-Visible Absorption Spectrum Analysis of the Nano-Packaging Materials Prepared in Example 1-2

[0228] Example 1: Prepare nano packaging material O-CMC-CA;

[0229] Example 2: Preparation of nano packaging material O-CMC-CM;

[0230] The test method is as follows:

[0231] S1: Weigh 10 mg of sample and dissolve it in 10 ml of deionized water, stir evenly at room temperature to remove insoluble impurities;

[0232] S2: Take 500 μl of the solution obtained in S1 and dilute it to 3 ml with deionized water;

[0233] S3: Use deionized water as the reference solution and perform spectral scanning using a UV spectrophotometer.

[0234] See also Figure 6(a), in the UV-visible spectrum of O-CMC-CA, the horizontal axis wavelength is the wavelength of light, the vertical axis indicates the absorbance, and the maximum absorption peak is located at 279nm, which is consistent with the absorption peak of the cinnamamide unit.

[0235] See also Figure 6 (b) In the UV-visible spectrum of O-CMC-CM, the horizontal axis wavelength is the wavelength of light and the vertical axis indicates absorbance. The spectral feature corresponding to the coumarin unit is observed at 320 nm.

[0236] Test Project 2: Study on the Photoresponsiveness of the Nano-Packaging Materials Prepared in Example 1-2

[0237] Example 1: Prepare nano packaging material O-CMC-CA;

[0238] Example 2: Preparation of nano packaging material O-CMC-CM;

[0239] The test method is as follows:

[0240] S1: Weigh 0.01 g of sample and dissolve it in 10 ml of deionized water;

[0241] S2: Use a xenon lamp (light power density of 6.45mW / cm 2 ) irradiate for 2, 4, 6, 8, 10, 15, 20, 25, 30, 35, 40 min, take 500 μL of the solution with different irradiation time, and dilute to 3 mL,

[0242] S3: (1) Use METTLER TOLEDO Easy Plus UV / Vis spectrophotometer to monitor the absorbance change trend of the sample;

[0243] (2) Use Lumina fluorescence spectrophotometer to monitor the fluorescence changes of samples.

[0244] 1. Test results of O-CMC-CA:

[0245] (1) In the UV-visible spectrum of O-CMC-CA, Figure 7 As shown in (a), the horizontal axis wavelength is the wavelength of light, and the vertical axis indicates absorbance. As the illumination time increases, the absorption of the polymer O-CMC-CA at around 270nm gradually decreases. This is due to the E / Z isomerization of the carbon-carbon double bond, that is, sunlight irradiation causes cinnamamide to isomerize to cis.

[0246] (2) In the fluorescence spectrum of O-CMC-CA, Figure 7As shown in (b), the horizontal axis wavelength is the wavelength of light, and the vertical axis indicates the fluorescence intensity. O-CMC-CA is fluorescent in nature, and the emission intensity gradually decreases with the increase of illumination time.

[0247] Therefore, the experiment proves that O-CMC-CA is responsive to light.

[0248] The photoresponse process of O-CMC-CA is as follows:

[0249] 2. Test results of O-CMC-CM:

[0250] (1) In the UV-visible spectrum of O-CMC-CM, Figure 8 As shown in (a), the horizontal axis wavelength is the wavelength of light, and the vertical axis indicates absorbance. As the illumination time increases, the absorption of the polymer O-CMC-CM at around 320nm gradually decreases.

[0251]

[0252] (2) In the fluorescence spectrum of O-CMC-CM, Figure 8 As shown in (b), the horizontal axis wavelength is the wavelength of light, and the vertical axis indicates the fluorescence intensity. O-CMC-CM has very excellent fluorescence properties, and the fluorescence intensity gradually decreases with the increase of illumination time.

[0253] Therefore, the experiment proves that O-CMC-CM is responsive to light.

[0254] The photoresponse process of O-CMC-CM is as follows:

[0255]

[0256] Test Item 3: Study on the Photoresponsiveness of the Nano-Packaging Material Prepared in Example 3

[0257] Example 3: Preparation of nano packaging material O-CMC-CZ;

[0258] The test method is as follows:

[0259] S1: Weigh 0.01 g of sample O-CMC-CZ, dissolve it in 10 ml of deionized water, and remove insoluble impurities;

[0260] S2: Use UV lamp (light power density is 2.2mW / cm 2 ) were irradiated for 0, 2, 4, 6, and 8 min, and the light response process of O-CMC-CZ was tracked using a UV-visible spectrometer.

[0261] The test results are as follows:

[0262] In the UV-visible spectrum of O-CMC-CZ, Fig. 9 As shown, the wavelength of light is the horizontal axis, and the absorbance is the vertical axis. After the compound 0-CMC-CZ was irradiated with ultraviolet light for 1 minute, the absorption intensity at around 348nm decreased rapidly, and the maximum absorption wavelength shifted slightly to the blue, which was due to the rapid twisting from the trans conformation to the cis conformation. The absorption intensity did not change significantly when the ultraviolet light irradiation time was extended.

[0263] Therefore, the compound is sensitive to ultraviolet light.

[0264] Test Item 4: Thermogravimetric analysis of the nano-packaging materials prepared in Examples 1-3 and comparison with carboxymethyl chitosan O-CMC

[0265] The test method is as follows:

[0266] The test was performed using a synchronous TG-DSC thermal analyzer (STA449F3-1053-M) under a nitrogen atmosphere at a heating rate of 10°C / min from 40°C to 800°C.

[0267] Thermogravimetric analysis results of O-CMC:

[0268] like Figure 10-12 As shown, in (a), the horizontal axis Temperature is temperature and the vertical axis is mass fraction, and in (b), the horizontal axis Temperature is temperature and the vertical axis is weight loss rate. When the temperature in the first stage increased to 80°C, the loss of adsorbed water occurred. In the second decomposition process, 0-CMC showed polysaccharide decomposition in the temperature range of 220-800°C, and it can be found that O-CMC reached the peak of the maximum decomposition rate at 269.7°C.

[0269] 1. Comparison between O-CMC-CA and O-CMC:

[0270] like Fig.10 As shown, the TGA and DTG curves of O-CMC and O-CMC-CA are compared. (a) is the TGA curve, with the horizontal axis Temperature being the temperature and the vertical axis being the mass fraction, and (b) is the DTG curve, with the horizontal axis Temperature being the temperature and the vertical axis being the weight loss rate. Through the observation of the DTG curve, after the introduction of the linking CA group, O-CMC-CA showed a maximum weight loss rate at 280°C, indicating that its thermal stability has been improved. Therefore, the introduction of the linking CA has effectively improved the thermal stability of O-CMC.

[0271] 2. Comparison between O-CMC-CM and O-CMC:

[0272] like Fig.11As shown, the TGA and DTG curves of O-CMC and O-CMC-CM are compared. (a) is the TGA curve, with the horizontal axis Temperature being the temperature and the vertical axis being the mass fraction, and (b) is the DTG curve, with the horizontal axis Temperature being the temperature and the vertical axis being the weight loss rate. Through the observation of the DTG curve, after the introduction of the linking CM group, O-CMC-CM showed the maximum weight loss rate at 277.8°C, indicating that its thermal stability has been improved. Therefore, the introduction of the linking CM has effectively improved the thermal stability of O-CMC.

[0273] 3. Comparison between O-CMC-CZ and O-CMC:

[0274] like Fig.12 As shown, the TGA and DTG curves of O-CMC and O-CMC-Z are compared. (a) is the TGA curve, with the horizontal axis Temperature being the temperature and the vertical axis being the mass fraction, and (b) is the DTG curve, with the horizontal axis Temperature being the temperature and the vertical axis being the weight loss rate. Through the observation of the DTG curve, after the introduction of the linking CZ group, 0-CMC-CZ showed the maximum weight loss rate at 276.3°C, indicating that its thermal stability has been improved. Therefore, the introduction of the linking CZ has effectively improved the thermal stability of O-CMC.

[0275] In summary, the nano packaging material prepared by the method of the present application is not easy to decompose even under high temperature conditions, and can make the nanoparticles stably exist in the mosquito repellent cream, which has application value.

[0276] Test Project 5: XRD Detection Research Experiment

[0277] Study subjects:

[0278] O-CMC; nano packaging materials O-CMC-CA, O-CMC-CM, O-CMC-CZ prepared in Examples 1-3; unloaded nanoparticles CMC-CA-Ca, CMC-CM-Ca, CMC-CZ-Ca prepared using the nano packaging materials prepared in Examples 1-3; DEET nanoparticles DEET / CMC-CA-Ca, DEET / CMC-CM-Ca, DEET / CMC-CZ-Ca prepared in Examples 1-3.

[0279] The test method is:

[0280] Set the scanning angle to 20, the X-ray voltage to 40KV, the tube current to 40mA, and the test rate to 5° / min to observe the changes in the crystal structure.

[0281] 1. Example 1 related

[0282] See also Fig.13(a), the horizontal axis is the diffraction angle, the vertical axis is the diffraction intensity. 0-CMC has a strong diffraction peak at 2θ=20°. Unlike 0-CMC, the peak of O-CMC-CA at 20° is significantly reduced, which may be due to the grafting of CA, which significantly reduces the crystallinity. In the unloaded nanoparticles CMC-CA-Ca, almost no diffraction peaks appear, which indicates that Ca 2+ With -COO - After cross-linking, the disorder of polymer chains increases, which significantly reduces the crystallinity of nanoparticles. The diffraction peaks of DEET / CMC-CA-Ca change significantly, with obvious peaks at 2θ=32.1°45.8°, 56.5°, indicating that there is a certain interaction between DEET and O-CMC-CA, not just a simple embedding effect.

[0283] 2. Example 2 related

[0284] See also Fig.13 (b), the horizontal axis is the diffraction angle, the vertical axis is the diffraction intensity. 0-CMC has a strong diffraction peak at 2θ = 20°. Unlike 0-CMC, the peak intensity of O-CMC-CM at a diffraction angle of 20° is greatly reduced. This may be due to the grafting of CM, which reduces the crystallinity and hydrogen bonding degree. In the unloaded nanoparticles CMC-CM-Ca, there is almost no diffraction peak, which indicates that Ca 2+ With -COO - After cross-linking, the disorder of polymer chains increases, which significantly reduces the crystallinity of nanoparticles. The diffraction peaks of DEET / CMC-CM-Ca change significantly, with obvious peaks at 2θ=31.7°45.5°.56.7°, indicating that there is a certain interaction between DEET and O-CMC-CM, not just a simple embedding effect.

[0285] 3. Example 3 related

[0286] See also Fig.13 (c), the horizontal axis is the diffraction angle, the vertical axis is the diffraction intensity. 0-CMC has a strong diffraction peak at 2θ = 20°. Unlike 0-CMC, the peak intensity of O-CMC-CZ at a diffraction angle of 20° is greatly reduced. This may be due to the grafting of CZ, which significantly reduces the crystallinity and hydrogen bonding. In the unloaded nanoparticles CMC-CZ-Ca, almost no diffraction peaks appear, which indicates that Ca 2+ With -COO -After cross-linking, the disorder of polymer chains increases, which significantly reduces the crystallinity of nanoparticles. The diffraction peaks of DEET / CMC-CZ-Ca change significantly, with obvious peaks at 2θ=31.7°, 45.5°, and 56.5°, indicating that there is a certain interaction between DEET and O-CMC-CZ, rather than just a simple embedding effect.

[0287] Test Item 6: Particle size and Zeta potential detection experiment of DEET / CMC-CA-Ca, DEET / CMC-CM-Ca, DEET / CMC-CZ-Ca

[0288] The test method is as follows:

[0289] The DEET nanoparticle suspension prepared in Example 1-3 was diluted with ultrapure water and uniformly dispersed by ultrasonication, and measured using a Malvern nanoparticle surface potential analyzer.

[0290] The test results are as follows:

[0291] 1. DEET / CMC-CA-Ca

[0292] like Fig.14 As shown in (a), the average particle size of the nanoparticles is 219.5 nm, the particle size distribution index (PDI) is 0.058, the encapsulation efficiency (EE) is 50.93%, the drug loading (LC) is 12.31%, and the Zeta potential is -15.1 mV.

[0293] These parameters indicate that DEET / CMC-CM-Ca has good performance.

[0294] 2. DEET / CMC-CM-Ca

[0295] like Fig.14 As shown in (b), the average particle size of the nanoparticles is 279.3 nm, the particle size distribution index (PDI) is 0.107, the encapsulation efficiency (EE) is 52.81%, the drug loading (LC) is 13.32%, and the Zeta potential is -14.1 mV.

[0296] These parameters indicate that DEET / CMC-CM-Ca has good performance.

[0297] 3. DEET / CMC-CZ-Ca

[0298] like Fig.14 As shown in (c), the average particle size of the nanoparticles was determined to be 240.3 nm, the particle size distribution index (PDI) was 0.025, in addition, the encapsulation efficiency (EE) reached 42.81%, the drug loading rate (LC) was 10.36%, and the Zeta potential was -14.2 mV.

[0299] These parameters indicate that DEET / CMC-CZ-Ca has good performance.

[0300] Test Item 7: Electron Microscope Morphology Detection Research Experiment on DEET / CMC-CA-Ca, DEET / CMC-CM-Ca, DEET / CMC-CZ-Ca

[0301] The test method is as follows:

[0302] The DEET nanoparticle suspension prepared in Example 1-3 was diluted and dropped onto aluminum foil, dried at room temperature, attached to a conductive adhesive, sprayed with gold under vacuum conditions, and the morphology was observed using a scanning electron microscope.

[0303] 1. DEET / CMC-CA-Ca

[0304] See also Fig.15 The prepared DEET / CMC-CA-Ca showed a regular square morphology, and its particle size ranged from approximately 100 to 250 nm.

[0305] 2. DEET / CMC-CM-Ca

[0306] See also Fig.16 The prepared DEET / CMC-CM-Ca has regular shape and good dispersion.

[0307] 3. DEET / CMC-CZ-Ca

[0308] See also Fig.17 The prepared DEET / CMC-CZ-Ca has a regular shape and a uniform distribution, and its particle size ranges from about 100 to 200 nm. It can be seen that the DEET nanoparticles prepared by the method of the present application have a regular shape, good dispersion, and a uniform particle size distribution, which is conducive to the uniform release of DEET.

[0309] Test Item 8: Light responsiveness study of DEET / CMC-CA-Ca, DEET / CMC-CM-Ca, and DEET / CMC-CZ-Ca

[0310] Study subjects:

[0311] Sample Group 1: Sample Group 1 was prepared in the same manner as Example 1 except for the amount of calcium chloride used in S24, except that the mass ratio of calcium chloride to nano-packaging material was 1:4, 1:5, 1:6, 1:7;

[0312] Sample Group 2: Sample Group 2 was prepared in the same manner as Example 2 except for the amount of calcium chloride used in S24, except that the mass ratio of calcium chloride to nano-packaging material was 1:4, 1:5, 1:6, 1:7;

[0313] Sample Group 3: Sample Group 2 was prepared in the same manner as Example 3 except for the amount of calcium chloride used in S24, except that the mass ratio of calcium chloride to nano-packaging material was 1:4, 1:5, 1:6, and 1:7.

[0314] The test method is as follows:

[0315] S1: Disperse the sample evenly;

[0316] S2: To avoid temperature changes of the solution due to light, the liquid obtained in S1 was placed under a simulated lamp for 5 min in an ice-water bath, and the particle size (Z-average), polymer dispersibility index (PDI) and Zeta potential (Zeta potential) were measured using a Malvern nanoparticle size surface potential analyzer.

[0317] 1. About sample set 1

[0318] The experimental results after sample illumination are shown in Fig.18 (a), the horizontal axis marks the mass ratio of calcium chloride to nano-packaging material, and the three bars in each group of bar graphs indicate the average particle size (z-average), polymer dispersibility index (PDI) and Zeta potential (Zeta potential) from left to right. After DEET / CMC-CA-Ca was exposed to simulated sunlight for 5 minutes, the particle size of the nanoparticles increased, but the Zeta potential and PDI did not change significantly. This phenomenon is caused by the photoresponsiveness of the cinnamamide group and the conformational change, which in turn leads to the increase in the particle size of the nanoparticles.

[0319] When DEET / CMC-CA-Ca is exposed to sunlight, the cinnamamide groups in it twist when exposed to light, changing the structure of the nanoparticles and thus changing the amount of drug released.

[0320] 2. About Sample Group 2

[0321] The experimental results after sample illumination are shown in Fig.18 (b). The horizontal axis indicates the mass ratio of calcium chloride to nano-packaging material. The three bars in each group of bar graphs indicate the average particle size (z-average), polymer dispersibility index (PDI) and Zeta potential (Zeta potential) from left to right. After exposing DEET / CMC-CM-Ca to simulated sunlight for 5 minutes, it can be observed that the particle size of the nanoparticles becomes smaller, while the Zeta potential and PDI do not change significantly. This phenomenon occurs due to the self-photoresponsiveness of the coumarin group and the change in its structure.

[0322] When DEET / CMC-CM-Ca is exposed to sunlight, the coumarin groups in it respond to light and change the structure of the nanoparticles, thereby changing the amount of drug released.

[0323] 3. About Sample Group 3

[0324] The experimental results can be found in Fig.18 (c). The horizontal axis marks the mass ratio of calcium chloride to nano packaging material, and the three bars in each group of bar graphs indicate the average particle size (z-average), polymer dispersibility index (PDI) and Zeta potential (Zeta potential) from left to right. After DEET / CMC-CZ-Ca was exposed to ultraviolet light for 5 minutes, the particle size of the nanoparticles was observed to decrease, but the Zeta potential and PDI did not change regularly. This phenomenon is caused by the conformational change of the azobenzene group in response to ultraviolet light. Then, DEET / CMC-CZ-Ca was placed under visible light, and the nanoparticle size was observed to increase, but it was still smaller than the initial particle size. This is because the azobenzene group, under the stimulation of visible light, realizes the transformation from cis conformation to trans conformation. Due to the existence of steric hindrance, the particle size increases but cannot be restored to the initial state.

[0325] When DEET / CMC-CZ-Ca is exposed to ultraviolet light, the azobenzene groups in it respond to the light and change the structure of the nanoparticles, thereby changing the amount of drug released.

[0326] In summary, the introduction of photoresponsive groups into carboxymethyl chitosan can achieve effective control of the particle size and structure of nanoparticles by light, and further affect the behavior of nanoparticles in releasing DEET.

[0327] Test Item 9: DEET Release Simulation Experiment

[0328] Experimental object: DEET nanoparticle suspension prepared in Examples 1-3

[0329] The test method is as follows:

[0330] S1: Weigh two portions of 10 mg DEET nanoparticle suspension and one portion of a control group nanoparticle suspension without DEET, disperse them in 3 mL PBS with a pH of 6.8 by ultrasonic, and illuminate one portion for 5 min;

[0331] S2: The three nanoparticle dispersions were placed into dialysis bags with a molecular weight cutoff between 8 and 14 KDa, respectively, and the dialysis bags were immersed in a container containing 40 ml of PBS solution;

[0332] S3: Place the three samples in a constant temperature oscillating box, set the temperature to 37°C and the rotation speed to 120 rpm for constant temperature oscillation.

[0333] S4: At the time points of 1, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 22, and 24 hours of shaking, 3 mL of solution was removed from the dialysate for testing, and 3 ml of fresh PBS medium was added to keep the total volume of the solution unchanged.

[0334] S5: Determine the DEET content in the sample using UV-Vis to determine the amount of DEET released from the DEET nanoparticles, using the dialysate of the unloaded DEET nanoparticle solution as the reference solution, and measure at a wavelength of 202nm. The cumulative amount of DEET released is calculated using the following formula:

[0335]

[0336] Where Ve is the sampling volume at the set time point Ve = 3 mL, V0 is the volume of the sustained-release solution V0 = 40 mL; Cn (mg / mL) is the concentration in the PBS solution at time n. mDEET is the total content of DEET encapsulated in the nanoparticles.

[0337] Test results:

[0338] 1. About Example 1

[0339] In S1, simulated sunlight is used to irradiate the sample for 5 minutes, and the light power density is 6.45mW / cm 2 .

[0340] See also Fig.19 , the horizontal axis is the illumination time, the vertical axis in (a) is the retention amount, and the vertical axis in (b) is the release amount. In the case of light protection, the release amount of the drug-loaded nanoparticles in 24 hours is 7.7%, and the retention amount is 92.3%. After 5 minutes of visible light irradiation, the release amount of the drug-loaded nanoparticles in 24 hours is 10.4%, and the retention amount is 89.6%.

[0341] After visible light irradiation, the release of drug-loaded nanoparticles increased slightly, which was due to the twisting of the cinnamamide group upon exposure to light, thus changing the drug release amount. Therefore, DEET / CMC-CA-Ca has good light responsiveness.

[0342] 2. About Example 2

[0343] In S1, simulated sunlight is used to irradiate the sample for 5 minutes, and the light power density is 6.45mW / cm 2 .

[0344] See also Fig. 20, the horizontal axis is the illumination time, the vertical axis in (a) is the retention amount, and the vertical axis in (b) is the release amount. In the case of light protection, the release amount of drug-loaded nanoparticles in 24 hours is 7.02%, and the retention amount is 92.98%. After 5 minutes of visible light irradiation, the release amount of drug-loaded nanoparticles is 10.94%, and the retention amount is 89.06%.

[0345] After visible light irradiation, the release of drug-loaded nanoparticles increased slightly, which is due to the twisting of the coumarin group upon exposure to light, thus changing the amount of drug released. Therefore, DEET / CMC-CM-Ca has good light responsiveness.

[0346] 3. About Example 3

[0347] In S1, ultraviolet light is used to irradiate the sample that needs to be illuminated for 5 minutes.

[0348] See also Fig.21 , the horizontal axis is the illumination time, the vertical axis in (a) is the retention amount, and the vertical axis in (b) is the release amount. In the case of light protection, the release amount of the drug-loaded nanoparticles in 24 hours is 6.0%, and the retention amount is 94%. After 5 minutes of visible light irradiation, the release amount of the drug-loaded nanoparticles in 24 hours is 6.5%, and the retention amount is 93.5%.

[0349] After visible light irradiation, the release amount of drug-loaded nanoparticles increased slightly, which is because the azobenzene group twisted when exposed to light, changing the pore size of the nanoparticles, thereby changing the drug release amount. Therefore, DEET / CMC-CZ-Ca has good light responsiveness.

[0350] Test Item 10: Simulation experiment on the slow release of DEET for mosquito repellent creams OCA, OCM and OCZ indoors and outdoors

[0351] The evaluation was performed by liquid chromatography, using a ThermoFisherScientificC 18 (250mm×5.6mm, 5μm, mobile phase is methanol: water (90:10), flow rate is 0.5ml / min, detection wavelength is 254nm, column temperature is 30℃.

[0352] Preparation of standard curve:

[0353] S1: Accurately weigh 0.01g DEET reference substance into a 25ml beaker, wash the beaker wall with isopropanol several times and transfer to a 10ml volumetric flask, shake to volume, and ultrasonicate for 1min to obtain a reference substance solution with a concentration of 1mg / ml;

[0354] S2: Use a pipette to measure 50μl, 100μl, 200μl, 300μl, and 400μl into a 10ml volumetric flask, add isopropanol to make up to volume and shake well to prepare standard solutions of 0.005mg / ml, 0.01mg / ml, 0.02mg / ml, 0.03mg / ml, and 0.04mg / ml.

[0355] The standard curve was prepared as Fig. 22 .

[0356] Sample preparation to simulate indoor conditions:

[0357] S1: Take 0.01g (0.0100-0.0109g) of sample into a 25ml beaker, use disposable gloves to evenly spread the sample on the wall of the beaker to simulate the process of applying cream on the human body. The mass must be kept unchanged during the spreading process. Place the sample in an oven at 32℃ (simulating human body surface temperature) with the lid open. Take out the beaker after 1h, 3h, 5h, 7h, and 10h, dissolve the remaining sample with isopropanol, wash several times and transfer to a 10ml volumetric flask, dilute and shake to obtain a sample solution with a concentration of 0.1mg / ml.

[0358] S2: Use a pipette to take 1 ml of the sample solution obtained at each time point into a 10 ml volumetric flask, dilute to volume with isopropanol and shake well again to obtain a solution with a concentration of 0.01 mg / ml.

[0359] Sample preparation for simulated outdoor conditions:

[0360] After applying the mosquito repellent cream, the sample was placed outdoors in full sunlight (28-35°C, wind level 2, gust level 4). The rest of the preparation process was the same as that for the simulated indoor samples.

[0361] The 15% concentration mosquito repellent cream OCA / OCM / OCZ was used as the control group for comparative testing, and the product with the same concentration, SC Johnson OFF, was used as the control group. SC Johnson OFF was selected because SC Johnson is the world's leading manufacturer of pest control products. OFF, as a sub-brand of SC Johnson specializing in mosquito control, is popular in tropical regions, especially in the Philippines, and is a more representative product of its kind.

[0362] Evaluation results:

[0363] 1. Embodiment 1

[0364] (1) Indoor simulation experiment

[0365]

[0366] Table 1: OCA time, peak area and corresponding values ​​of residual DEET concentration

[0367] The experimental results are as follows Fig.23As shown, (a) is the corresponding relationship curve between the indoor release time and peak area of ​​OCA and the release time and residual amount, and (b) is the time-concentration comparison diagram of OCA and the control group, and OFF in (b) refers to the control group. Referring to Table 1, the retention amount of DEET after 10 hours is 60%, indicating that the mosquito repellent cream OCA still has the effect of repelling mosquitoes after 10 hours. At the same concentration, the net DEET content of the mosquito repellent cream OCA is 9% after 10 hours; while in the control group, the net DEET content of 10 hours is 6.52%. After 10 hours, the DEET content of the mosquito repellent cream OCA is 2.48% higher than that of the control group.

[0368] (2) Outdoor simulation experiment

[0369]

[0370] Table 2: OCA time, peak area and corresponding values ​​of residual DEET concentration

[0371] The experimental results are as follows Fig.26 As shown in Table 2, the retention amount of DEET after 10 hours is 62%, indicating that the mosquito repellent cream OCA still has the mosquito repellent effect after 10 hours.

[0372] 2. Embodiment 2

[0373] (1) Indoor simulation experiment

[0374]

[0375] Table 3: OCM time, peak area and corresponding values ​​of residual DEET concentration

[0376] The experimental results are as follows Fig.24 As shown, (a) is the corresponding relationship curve between the indoor release time and peak area of ​​OCM and the release time and residual amount, (b) is the time-concentration comparison diagram of OCM and the control group, and OFF in (b) refers to the control group. See Table 3, the retention amount of DEET after 10 hours is 58%, indicating that the mosquito repellent cream OCM still has the effect of repelling mosquitoes after 10 hours. At the same concentration, the net DEET content of the mosquito repellent cream OCM 10 hours is 8.7%; the net DEET content of the control group 10 hours is 6.52%. After 10 hours, the DEET content of the mosquito repellent cream OCM is 2.18% higher than that of the control group.

[0377] (2) Outdoor simulation experiment

[0378]

[0379] Table 4: OCM time, peak area and corresponding values ​​of residual DEET concentration

[0380] The experimental results are as follows Fig.26As shown in Table 4, the retention amount of DEET after 10 hours is 61%, indicating that the mosquito repellent cream OCM still has the mosquito repellent effect after 10 hours.

[0381] 3. Embodiment 3

[0382] (1) Indoor simulation experiment

[0383]

[0384] Table 5: OCZ time, peak area and corresponding values ​​of residual DEET concentration

[0385] The experimental results are as follows Fig.25 As shown, (a) is the corresponding relationship curve between the indoor release time and peak area of ​​OCZ and the release time and residual amount, (b) is the time-concentration comparison diagram of OCZ and the control group, and OFF in (b) refers to the control group. See Table 5, the retention amount of DEET after 10 hours is 63%, indicating that the mosquito repellent cream OCZ still has the effect of repelling mosquitoes after 10 hours. At the same concentration, the net DEET content of the mosquito repellent cream OCZ after 10 hours is 9.4%; the net DEET content of the control group after 10 hours is 6.52%. After 10 hours, the DEET content of the mosquito repellent cream OCZ is 2.88% higher than that of the control group.

[0386] (2) Outdoor simulation experiment

[0387]

[0388] Table 6: OCZ time, peak area and corresponding values ​​of residual DEET concentration

[0389] The experimental results are as follows Fig.26 As shown in Table 6, the retention amount of DEET after 10 hours is 63%, indicating that the mosquito repellent cream OCZ still has the mosquito repellent effect after 10 hours.

[0390] Test Item 11: Live Mosquito Test of Mosquito Repellent Cream OCA, OCM, OCZ

[0391] The test was carried out according to GB / T13917.9-2009 standard Part 9: Repellents.

[0392] The DEET concentration in the control group and Examples 1-3 was 15%

[0393] Test conditions: The temperature was maintained at 26℃~30℃ and the relative humidity was maintained at 65%±10%.

[0394] Mosquito attack test: 100 female mosquitoes that have emerged for 3 to 5 days and have not sucked blood are placed in a mosquito cage (40 cm long, 30 cm wide, and 30 cm high). The tester's back of hand is exposed to 4 cm*4 cm of skin, and the rest of the hand is tightly covered. Put your hand into the mosquito cage and stay there for 2 minutes. Observe carefully. If you find mosquitoes landing, shake them away before biting, it is recorded as one test insect landing. If more than 10 test insects land on the tester and the test insects, the attack power is qualified, and this person and the mosquito cage can be used for repellent experiments.

[0395] Mosquito repellent test: 4 testers who passed the attack test were selected, and a 5*5cm area was drawn on the back of each of their hands. The repellent to be tested (1.5mg / cm 2 ), expose 4cm*4cm of the skin, and strictly protect the rest of the hand. The other hand is a blank control. 1 hour after applying the repellent, put your hand into the mosquito cage for 2 minutes to observe whether there are mosquitoes coming to land and suck blood. After that, test once every 1 hour. As long as there is a mosquito sucking blood, the repellent is considered ineffective. Record the effective protection time (h) of the repellent. A blank control test should be performed first at each time point to ensure the accuracy of the experimental results. Test insects with qualified attack power can continue the experiment, and those that fail need to be replaced.

[0396] Test results:

[0397] 1. See Fig. 27 , the mosquito repelling effect of embodiment 1 is as follows:

[0398] OCA can effectively repel mosquitoes for 6.8 hours, which is at least 2 hours longer than the control group.

[0399] time Mosquito repellent effect of the control group OCA mosquito repellent effect 1h Mosquitoes are 0.5 cm away from the skin The mosquito is 1-2cm away from the skin 1-2h Mosquitoes are 0.1cm away from the skin The mosquito is 1-2cm away from the skin 2-4h Mosquitoes stay for 1 second and fly away Mosquitoes are 0.5 cm away from the skin 4.5-5h Mosquitoes start biting Mosquitoes are 0.1cm away from the skin 5-6h / Mosquitoes stay for 1 second and fly away 6.8h / Mosquitoes start biting

[0400] 2. See Fig.28 The mosquito repelling effect of Example 2 is as follows:

[0401] time Mosquito repellent effect of the control group OCM mosquito repellent effect 1h Mosquitoes are 0.5 cm away from the skin The mosquito is 1-2cm away from the skin 1-2h Mosquitoes are 0.1cm away from the skin The mosquito is 1-2cm away from the skin 2-4h Mosquitoes stay for 1 second and fly away Mosquitoes are 0.5 cm away from the skin 4.5-5h Mosquitoes start biting Mosquitoes are 0.1cm away from the skin 5-6h / Mosquitoes stay for 1 second and fly away 6.8h / Mosquitoes start biting

[0402] Therefore, the effective mosquito repellent time of OCM was 6.8 hours, which was at least 2 hours longer than that of the control group.

[0403] 3. See Fig.29 The mosquito repelling effect of Example 3 is as follows:

[0404] time Mosquito repellent effect of the control group OCZ mosquito repellent effect 1h Mosquitoes are 0.5 cm away from the skin The mosquito is 1-2cm away from the skin 1-2h Mosquitoes are 0.1cm away from the skin The mosquito is 1-2cm away from the skin 2-4h Mosquitoes stay for 1 second and fly away Mosquitoes are 0.5 cm away from the skin 4.5-5h Mosquitoes start biting Mosquitoes are 0.1cm away from the skin 5-6h / Mosquitoes stay for 1 second and fly away 6.8h / Mosquitoes start biting

[0405] Therefore, the effective mosquito repellent time of OCZ is 6.8 hours, which is at least 2 hours longer than that of the control group.

[0406] In the description of this specification, the description with reference to the terms "preferred embodiment", "further embodiment", "other embodiments" or "specific example" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0407] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A mosquito repellent cream, characterized in that: The invention comprises, by weight, 15-25 parts of stearic acid, 15-25 parts of paraffin, 2-6 parts of cetyl stearic acid, 2-6 parts of hexadecanol, 1-5 parts of glyceryl monostearate, 5-15 parts of polyethylene glycol monostearate, 1-10 parts of glycerol, 40-80 parts of water, 5-15 parts of cross-linked polyvinyl pyrrolidone, 20-40 parts of DEET, and 20-40 parts of DEET nanoparticle suspension.

2. The mosquito repellent cream according to claim 1, characterized in that: The invention comprises, by weight, 17-23 parts of stearic acid, 17-23 parts of paraffin, 3-5 parts of spermaceti, 3-5 parts of hexadecanol, 2-4 parts of glyceryl monostearate, 7-13 parts of polyethylene glycol monostearate, 4-8 parts of glycerol, 50-70 parts of water, 7-13 parts of cross-linked polyvinyl pyrrolidone, 25-35 parts of DEET, and 25-35 parts of DEET nanoparticle suspension.

3. The mosquito repellent cream according to claim 1, characterized in that: The average particle size x in the DEET nanoparticle suspension satisfies 100nm≤x≤300nm.

4. The mosquito repellent cream according to claim 1, characterized in that: The DEET nanoparticle suspension comprises nanoparticles, wherein the nanoparticles are formed by encapsulating DEET in a complex of a carboxymethyl chitosan derivative and calcium ions; the carboxymethyl chitosan derivative is prepared by modifying carboxymethyl chitosan with a compound having a photoresponsive group, wherein the photoresponsive group is a cinnamic acid group, a coumarin group or an azobenzene group.

5. The mosquito repellent cream according to claim 1, characterized in that: The DEET nanoparticle suspension is prepared by the following steps: (1) Preparation of nano packaging materials: S11: dissolving a monomer having a photoresponsive group in dimethyl sulfoxide, adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide, and stirring to activate the monomer in a light-proof condition; S12: dissolving carboxymethyl chitosan in deionized water to prepare an aqueous solution; S13: The solution obtained in S11 and the solution obtained in S12 are mixed, tetramethylethylenediamine is added, and the mixture is stirred and reacted at room temperature in the dark to obtain a light yellow transparent solution; S14: dialyzing the solution obtained in S13 with deionized water; S15: freeze-drying the product obtained in S14 to obtain the nano packaging material; (2) Preparation of nanoparticle suspension: S21: preparing the nano-package obtained in S15 into an aqueous solution to remove insoluble impurities; S22: adjusting the pH of the solution obtained in S21 to 6.5-8; S23: preparing a DEET ethanol solution, and adding the DEET ethanol solution dropwise into the solution obtained in S22; S24: adding the calcium chloride solution dropwise to the solution obtained in S23, and continuing stirring until the reaction is complete; S25: sedimentation under an inert atmosphere to obtain the DEET nanoparticle suspension.

6. The mosquito repellent cream according to claim 5, characterized in that: The monomer having a photoresponsive group is one or more of cinnamic acid, coumarin derivatives and azobenzene derivatives.

7. The mosquito repellent cream according to claim 6, characterized in that: The structural formula of the coumarin derivative is:

8. The mosquito repellent cream according to claim 6, characterized in that: The structural formula of the azobenzene derivative is:

9. The mosquito repellent cream according to claim 1, characterized in that: The mosquito repellent cream consists of 19-21 parts of stearic acid, 19-21 parts of paraffin, 3.5-4.5 parts of spermaceti, 3.5-4.5 parts of hexadecanol, 2.5-3.5 parts of glyceryl monostearate, 9-11 parts of polyethylene glycol monostearate, 5-7 parts of glycerol, 58-68 parts of water, 0.1-0.3 parts of Kaisong CG, 9-11 parts of cross-linked polyvinyl pyrrolidone, 28-32 parts of DEET, and 28-32 parts of DEET nanoparticle suspension, in parts by weight.

10. The mosquito repellent cream according to claim 1, characterized in that: The preparation method of the mosquito repellent cream comprises the following steps: S31: heating and mixing the stearic acid, paraffin, cetyl stearic acid, hexadecanol, glyceryl monostearate, and polyethylene glycol monostearate to obtain phase A; heating and mixing the glycerin and water to obtain phase B; mixing the cross-linked polyvinyl pyrrolidone and DEET to obtain phase C; S32: mixing the phase A and the phase B in a homogenizer; S33: adding phase C into the homogenizer and mixing; S34: putting the DEET nanoparticle suspension into the homogenizer for mixing.